2008
DOI: 10.1002/adem.200800142
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Demonstration of Entrance/Exit Effects on the Permeability Measurements of Porous Materials

Abstract: The pressure drops were measured on metallic foams having uniform structure and different thicknesses, densities and pore sizes. Results indicated that entrance/exit effects can be a significant contributor to the pressure drop when the thickness of the specimens is small. Above a critical thickness, the contribution of the entrance effect on the total pressure drop becomes insignificant and classical models can be applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 11 publications
(17 reference statements)
4
38
0
Order By: Relevance
“…Entrance and exit effects were observed in pressure drop measurements performed on several commercial open-cell metal foams by Baril et al (2008). Results showed the pressure gradient to be dependent on the sample thickness in the direction of flow.…”
Section: Introductionmentioning
confidence: 97%
“…Entrance and exit effects were observed in pressure drop measurements performed on several commercial open-cell metal foams by Baril et al (2008). Results showed the pressure gradient to be dependent on the sample thickness in the direction of flow.…”
Section: Introductionmentioning
confidence: 97%
“…This "critical thickness" has been reported in several other studies and is a function of the pore size. Typically, thickness-independent behaviour is observed in the laminar flow region for flow distances exceeding 40-50 pore diameters [3,9].…”
Section: Length-normalised Pressure Drop and Regime Changementioning
confidence: 99%
“…The pressure-drop across monolithic (bulk) porous metals has been widely investigated, including studies reported in [1][2][3][4][5][6]. In many engineering systems, for low (laminar) flow velocities, the relationship between pressure-drop and airflow velocity is ably described by the Hazen-Darcy or Forchheimer equation [3,7,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations